2021
DOI: 10.33448/rsd-v10i8.17125
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of the pandemic on caregivers of older adults: A rapid systematic review

Abstract: The COVID-19 pandemic has rendered numerous impacts on society, especially to caregivers of older adults, who are facing many tasks. These elevated number of demands and modifications can affect these caregivers’ mental health. This study aimed to gather empirical evidence on existing researches about the impact of caregiver’s mental health of older adults during the COVID-19 pandemic. This rapid systematic review, developed from international and Brazilian databases from January/2020 to April/2021, identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(52 reference statements)
1
0
0
Order By: Relevance
“…Family caregivers could also care for older individuals with special health needs, and their experience could be different than the experiences of parents of children with disabilities in the present study. Nevertheless, a rapid systemic review reported that family caregivers of individuals with Alzheimer’s disease and other dementias reported a high increase level of burden, anxiety, depression, and distress [ 32 ], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Family caregivers could also care for older individuals with special health needs, and their experience could be different than the experiences of parents of children with disabilities in the present study. Nevertheless, a rapid systemic review reported that family caregivers of individuals with Alzheimer’s disease and other dementias reported a high increase level of burden, anxiety, depression, and distress [ 32 ], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%